Comparison of Induction Chemotherapy Plus Concurrent Chemoradiotherapy and Concurrent Chemoradiotherapy Alone in Locally Advanced Nasopharyngeal Carcinoma. (28th January 2021) - Xu, Guoqiang; Wang, Qiaoli; Wu, Xingrao; Lv, Chunyan; Zeng, Guilin; Xue, Zhihong; Cao, Ruixue; Zhang, Nan; Xiong, Wei; Huang, Qin
Purpose: Induction chemotherapy plus concurrent chemoradiotherapy and concurrent chemoradiotherapy alone are both standard treatment regimens for managing locally advanced nasopharyngeal carcinoma. However, the results of comparisons between them in clinical trials vary. Therefore, we designed this meta-analysis to illustrate their advantages and disadvantages in patients with locally advanced nasopharyngeal carcinoma. Methods: We thoroughly searched the PubMed, EMBASE, and Cochrane Library databases and then merged the effect indicators of hazard ratios and risk ratios using RevMan 5.1. Results: Seven randomized controlled trials totaling 2, 319 patients were included in our research. The synthesized results showed that induction chemotherapy plus concurrent chemoradiotherapy improved overall survival (HR = 0.75, 95% CI: 0.63-0.89, P = 0.001), progression-free survival (HR = 0.69, 95% CI: 0.60-0.80, P < 0.001), distant metastasis-free survival (HR = 0.65, 95% CI: 0.53-0.80, P < 0.001) and locoregional recurrence-free survival (HR = 0.68 95%, CI: 0.54-0.86, P = 0.001) versus concurrent chemoradiotherapy alone. It also increased the risk of anemia, thrombocytopenia, and neutropenia during concurrent chemoradiotherapy. However, the incidence of leukopenia and mucositis was similar in induction chemotherapy and induction chemotherapy plus concurrent chemoradiotherapy. Furthermore, the subgroup analysis showed better survival outcomes with induction chemotherapy plus concurrent chemoradiotherapy than with concurrent chemoradiotherapy alone in the triweekly cisplatin subgroup (all P < 0.01), whereas induction chemotherapy plus concurrent chemoradiotherapy could only improve progression-free survival and locoregional recurrence-free survival in the weekly cisplatin subgroup (HR = 0.78, P = 0.02; and HR = 0.66, P = 0.03, respectively). Conclusions: Induction chemotherapy plus concurrent chemoradiotherapy improved survival outcomes in patients with locally advanced nasopharyngeal carcinoma versus concurrent chemoradiotherapy. For the weekly cisplatin regimen subgroup, it did not improve remote control or overall survival versus concurrent chemoradiotherapy alone, warranting further clarification.